Pengaturan Mekanisme Pasar dengan Persepsi Hisbah - Kimia Us Sa’adah; Luthfia Zahra Sakinah; Zahra Raudhotun Najjah (Journal of Islamic Economics and Finance, 2025)
Islam is a religion that requires trading, the Prophet is a good role model in teaching trading rules, in this research we examine the regulation of market mechanisms with the perception of hisbah using the review literature review method, and study the comparison of sharia and conventional trading objects in Indonesia, so as to create a fair trading system and healthy competition in the trading market.